2003
DOI: 10.1586/14737159.3.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in cancer: the application of microarrays

Abstract: Genome-wide monitoring of gene expression using DNA microarrays represents one of the latest breakthroughs in experimental molecular biology and provides unprecedented opportunity to explore the biological processes underlying human diseases by providing a comprehensive survey of a cell's transcriptional landscape. In the cancer field, this revolutionary technology allows the simultaneous assessment of the transcription of tens of thousands of genes, and of their relative expression between normal cells and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 31 publications
0
26
0
1
Order By: Relevance
“…A major focus of biomedical research in the post-genomic era is the systematic analysis of gene expression patterns and protein profiles of cells, tissues, and body fluids with the goal of identifying molecular ''signatures'' characteristic of particular disease states (1,2). RNA or protein profiling can be exploited to assess similarities and differences in the expressed genome and/or proteome of tumors with identical histology and to classify tumors based on a given molecular profile (3).…”
Section: Introductionmentioning
confidence: 99%
“…A major focus of biomedical research in the post-genomic era is the systematic analysis of gene expression patterns and protein profiles of cells, tissues, and body fluids with the goal of identifying molecular ''signatures'' characteristic of particular disease states (1,2). RNA or protein profiling can be exploited to assess similarities and differences in the expressed genome and/or proteome of tumors with identical histology and to classify tumors based on a given molecular profile (3).…”
Section: Introductionmentioning
confidence: 99%
“…The invention of technologies for transcriptomics, using genome-wide analysis and computational approaches, has made it possible to identify the prognostic significance of individual gene expression changes from thousands of markers. For example, in cancer studies, this technology is employed to obtain comprehensive gene expression profiles in both normal tissues (Saito-Hisaminato et al, 2002) and cancer tissues including those from hepatocellular carcinomas, pancreatic cancers, and esophageal squamous cell carcinomas (Okabe et al, 2001;Han et al, 2002;Macgregor, 2003;Nakamura et al, 2004;Yamabuki et al, 2006;D Angelo et al, 2014;Zhu and Tsao, 2014;Nishimura et al, 2015). Using microarrays, biomarkers for Parkinson s disease (Alonso-Navarro et al, 2014;Sun et al, 2014) and myocardial infarction (Devaux et al, 2010;G ogowska-Ligus and D bek, 2012) have been identified.…”
Section: Evaluation For Diseasesmentioning
confidence: 99%
“…Such cDNA expression studies have led to a number of exciting breakthroughs in basic science. For example, microarray analysis of certain tumours has been successful in correlating particular expression patterns with patient prognosis (Macgregor, 2003). Microarrays of cDNA expression have also been used effectively as predictors of success for hormone responsiveness, hormone non-responsiveness, clinical outcomes and anticancer chemotherapeutic drugs (Domchek & Weber, 2002;Liu & Karuturi, 2004), even if other phenotypes may also be directly related to drug response.…”
Section: Complementary Approachesmentioning
confidence: 99%